Jefferson Davis, Confederate president - Hattaway, Herman; Beringer, Richard E., 1933-2020. (Lawrence : University Press of Kansas, 2002)
He was one of the most embattled heads of state in American history. Charged with building a new nation while waging a war for its very independence, he accepted his responsibilities reluctantly but carried them out with a fierce dedication to his ideals. Those efforts ultimately foundered on the shoals of Confederate defeat, leaving Davis stranded in public memory as bot valiant leader and desolate loser. Now two renowned Civil War historians, Herman Hattaway and Richard Beringer, take a new and closer look at Davis's presidency. In the process, they provide a clearer image of his leadership and ability to handle domestic, diplomatic, and military matters under the most trying circumstances--without the considerable industrial and population resources of the North and without the formal recognition of other nations. Hattaway and Beringer examine Davis's strengths and weaknesses as president in light of both traditional evidence and current theories of presidential leadership. They show us a man so respected that northern colleagues regretted his departure from the U.S. Senate, but so bent on southern independence that he was willing to impose unthinkable burdens on the citizens of the Confederate States--an apologist for slavery who was committed to state rights, even while growing nationalism in his new country called for a stronger central government. In assessing Davis's administration of the Confederate States, the authors analyze the Confederate government's constitution, institutions, infrastructure, and cabinet-level administrators. They also integrate events of Davis's presidency with the on-going war as it encroached upon the South, offering a panoramic view of military strategy as seen from the president's office. They tell how Davis reacted to the outcomes of key battles and campaigns in order to assess his leadership abilities, relations with civilian and military authorities, and--his own personal competency notwithstanding--poor judgment in selecting generals.
What manner of man? -- The establishment of government -- Provisional administration -- To Sumter -- Plates : persons -- The wait for land battles -- In the aftermath of first Manassas -- Forging the resources of war -- Northern power emerges -- Escalating degrees of warfare -- The threat of emancipation -- Union power affirmed -- The meaning of the war -- Plates : places -- War leadership in supreme test -- The great hope : that Lincoln be denied reelection -- The winter of great discontent -- The battlefield realities in 1865 -- The end in Virginia -- The pseudo-Confederacy -- Plates : art and community -- Barber's model of presidential leadership.
Includes bibliographical references (p. [509]-523) and index.
Keywords: Davis, Jefferson, -- 1808-1889.; Presidents -- Confederate States of America -- Biography; Confederate States of America -- Politics and government; United States -- History -- Civil War, 1861-1865 -- Campaigns; Confederate States of America -- Biography; Statesmen -- United States -- Biography